Identification of blood immunological biomarkers of SARS-CoV-2 infection during pandemic in Poland - Leśniak, Monika; Borkowska, Agata; Kłos, Krzysztof; Aleksandrowicz, Karolina; Porębska, Klaudia; Kobza, Dagmara; Piwowarek, Krzysztof Łukasz; Plewka-Barcik, Katarzyna; Niemcewicz, Marcin; Lutyńska, Anna; Kubiak, Jacek Z.; Chciałowski, Andrzej; et al. (Frontiers in Immunology, 2025)
IntoductionT lymphocytes, along with cytokines and chemokines-dependent pathways are primarily responsible for regulating the immune response, controlling inflammation and eliminating viral infections. However, excessive immune activity can lead to pathological effects such as cytokine storm, which may cause severe respiratory distress syndrome and multi-organ damage in COVID-19. The aim of this study was to identify potential biomarkers of SARS-CoV-2 infection that could predict the severity of COVID-19 progression.MethodsThe cohort in this study included 52 hospitalized adult patients with SARS-CoV-2 infection from Warsaw, Poland admitted to the hospital during COVID-19 pandemic (February to November 2021). Based on clinical symptoms, patients were divided into two groups: (i) mild/moderate symptoms (non-severe) – 44 patients and (ii) severe respiratory failure (severe) – 8 patients. The control group consisted of 26 individuals without COVID-19. All COVID-19 patients and healthy controls underwent immunophenotyping of peripheral blood to assess the abundance of T lymphocytes and regulatory T lymphocytes, as well as measurement of selected cytokine and chemokine concentrations in corresponding serum samples. Data analysis was performed using CytoFLEX Flow Cytometer. Results and discussionDecreased percentages of total lymphocytes and T lymphocytes in peripheral blood were observed across all COVID-19 patients, with varying degrees between the non-severe and severe groups. A significant reduction was also noted in double-positive lymphocytes (CD4+CD8+), regulatory T lymphocytes ( CD4+ CD25HiCD127Lo and CD4+CD25HiCD127LoFoxP3+), as well as CD4+CD25+/-, CD4+CD45RA+/-, and CD8+CD45RA+/- subsets. Elevated levels of IL-6, IL-10, IL-17A, IFN-g, CCL2, CXCL8, and CXCL10 were observed in the non-severe and/or severe groups compared to healthy controls. Most importantly, only CXCL10 was significantly elevated in the severe group at admission compared to the non-severe group. In this study, we identified the chemokine CXCL10 as a crucial marker for distinguishing the severe course of COVID-19 from non-severe form at the time of admission. It may serve as an early indicator of diseases progression during hospitalization, potentially allowing prediction of the disease course. Moreover, elevated CXCL10 levels, in combination with decreased total lymphocytes counts and increased levels of IL-6, IL10, IFNg, CCL2 and CXCL9, may represent a more comprehensive biomarker panel suitable for predicting the severity of COVID-19.